Faculty Experiences Developing and Implementing Policies for Exit Exam Testing. Issue 4 (July 2015) - Stonecypher, Karen; Young, Anne; Langford, Rae; Symes, Lene; Willson, Pamela
Abstract : Nursing schools use standardized exit examinations to determine student readiness for the NCLEX-RN. Yet little is known about how nursing programs develop policies for using the examinations, set benchmarks scores, and implement remediation strategies with their students. In a phenomenological study, faculty identified a testing policy process that fell into the major themes of triggers for change, policy modification, and reactions to change.